Check out our new programming micro service marketplace:

BanaNibble.com

Get a plagiarism check of an answer before you buy it. See more details here

find the horizontal asymptote of y=(4e^(x) + 7)÷(e^(x)-1)

body preview (19 words)

horizontal asymptotes x = (4e^x x 7)/(e^x x 1) xx > xx x = 0 , x = + xxxxxxxx hence, xxxxxxxxxx asymptote is x x inf.

Buy this answer

body preview (26 words)

xxx hor asyptote slope xxxx xx 0 so dy/dx=(e^x-1)(4e^x)-(4e^x+7)(e^x)=0 for this x u xxxx get xxxx xxxxxxxxxx